PENGARUH MODEL PEMBELAJARAN PROBLEM BASED RESEARCH (PBR) BERBANTUAN ARTIKEL KIMIA TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA MATERI SISTEM KOLOID - Mira Adriani; Khaeruman Khaeruman; Dahlia Rosma Indah (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
One of colloid system subject material characteristicis abstract concepts causing students difficulties to understand it, so that the student critical thinking ability and learning outcomes is low. This study aims to determine the effect of Problem Based Reasearch (PBR) model assisting withchemistry articles on studentcritical thinking skills and learning outcomes. In form of quasi experimental, this research was carried out by Posttest Only Control Group Design with all 40 amount students of class XI IPA as poppulation who divided into 2 classes. Through saturated sampling, so that IPA 1 class as experiment class and IPA 2 class as control class. The data was collected byessay and multiple choice test. Data were analyzed by t-test statistic. The result of critical thinking skilldata analysis obtained t count = 3.19 with, ttable = 1.687 at df = 38 and significant level 5%. Because tcount> ttable (3.19> 1.687) then the null hypothesis (H0) proposed is rejected and Ha accepted. While learning outcomes data analysis obtained t count = 0.88 ttable = 1.687 at df = 38 and a significant level 5%. Because t count< ttable (0.88< 1.687) then the proposed null hypothesis (H0) is accepted and Ha is rejected. Based on the research results, it can be concluded that the application of Problem Based Research (PBR) model assited chemistry article has an effect on critical thinking skill and has no effect on student learning outcomes.